KINERJA ORGANISASI BIDANG LALU LINTAS DINAS PERHUBUNGAN DAERAH ISTIMEWA YOGYAKARTA (DIY) GUNA MENCIPTAKAN KEBIJAKAN YANG EFEKTIF DAN AKUNTABEL (Studi Kasus Dinas Perhubungan Daerah Istimewa Yogyakarta) - Hutama Taufiq Rizqi; Yaqub Cikusin; Hayat Hayat (Sekolah Tinggi Pariwisata Mataram, 2021)
The Yogyakarta Special Region Transportation Service Office is led by a head of service who is responsible for the Mayor of the Special Region of Yogyakarta. The Office of the Department of Transportation which is located in Jl. Babarsari No. 30 Yogyakarta City, Yogyakarta Special Region 55163. The initial objective in taking this title was to determine the performance of the Yogyakarta Special Region Traffic Department of Transportation, and to find out the inhibiting factors and how to overcome them to improve the performance of the Yogyakarta Special Region Traffic Transportation Service. This research method uses qualitative methods. Data collection methods are documentation and interviews as data. This study obtained the results that there are inhibiting factors in the performance of the Department of Transportation for the Traffic Division of the Special Region of Yogyakarta.